2021
DOI: 10.1088/1361-6463/abde6b
|View full text |Cite
|
Sign up to set email alerts
|

Short-range magnetic behavior in manganites La0.93K0.07Mn1- x Cu x O3 (0.0 ⩽ x ⩽ 0.09) above the Curie temperature

Abstract: Manganites La0.93K0.07Mn1−x Cu x O3 ( 0.0 ⩽ x ⩽ 0.09 ) , prepared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 37 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…Perovskite manganites have been the subject of intense research efforts [1][2][3][4][5] due to the potential technological application of the so-called colossal magnetoresistance (CMR) behavior. [6][7][8] In the last two decades, experiments have focused on the effects of the application of an electric eld on doped manganites. These systems are known to exhibit interesting electronic properties which are explained by many mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Perovskite manganites have been the subject of intense research efforts [1][2][3][4][5] due to the potential technological application of the so-called colossal magnetoresistance (CMR) behavior. [6][7][8] In the last two decades, experiments have focused on the effects of the application of an electric eld on doped manganites. These systems are known to exhibit interesting electronic properties which are explained by many mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…These clusters have been, in all cases, related to the mentioned random magnetic disorder. [ 10–16 ] Also, it has been observed that in most of the LaMn 0 3 ceramics doped, both at the La site as in the Mn site, the inverse magnetic susceptibility χ 1 ( T ) in a certain regime above long‐range order, T * > T normalC , does not follow the Curie Weiss (CW) law, χ 1 = ( T θ CW ) / C , where C and θ CW are Curie constant and paramagnetic (PM) CW temperature, respectively. This law is the asymptotic behavior of magnetization at T T normalC .…”
Section: Introductionmentioning
confidence: 99%